Impact of early learning and child care on the parents of children pre-school children: results of a rapid systematic review. (November 2017) - Pringle, Jan; Scobie, Graeme; Arnot, Julie; Doi, Lawrence; McAteer, John; Scott, Eileen; Reid, Garth
Abstract: Background: The Scottish Government aims to make Scotland the best place in the world to grow up in for children and families. To realise this vision, strategic policy changes intend to ensure that increased access to funded early learning and child care (ELC) is available. This will facilitate parental employment, or enable re-entry to education and training, while children are cared for in safe, stimulating environments. To inform this vision, the Public Health Evidence Network was asked to provide evidence on the impact of ELC on parental outcomes. This study aimed to investigate the impact of early learning and child care on parents with pre-school children across a broad range of countries. Methods: A rapid systematic review was conducted from June 1 to Sept 30, 2016. Two reviewers independently assessed papers for eligibility, using a protocol aligned to the PRISMA-R guidelines. Databases searched were Medline, ERIC, EMBASE, EConLit, Education Abstracts, Education Source, Web of Science, ASSIA, Sociological Abstracts, IBSS, PsycINFO, and the British Education Index. Key and text words associated with early learning, child care, parents, young children, and employment were adapted for use across all databases. All English language publication types and research designs were sought, to enable inclusion of primary studies and expert (grey literature) reports. Because of heterogeneity of study type, methods, and outcome measures, meta-analysis and quality appraisal were not feasible. A narrative analysis, using a tabulated system that facilitated cross-checking of results across studies, was done to produce a fuller understanding of factors beyond cause and effect. Findings: Of 5442 initial papers, 54 met the inclusion criteria. Analysis revealed two main areas of focus—namely, those pertaining to ELC provision (flexibility, availability, affordability, and quality), and those that related to parental impact (employability, socioeconomic issues, and health and wellbeing). Interpretation: Our findings support the case that affordable and accessible ELC can potentially mitigate the impacts of economic and social disadvantage by facilitating parental, particularly maternal, employment and employability, thus serving a redistributive function. However, policy must ensure that affordability, flexibility, and availability meet the needs of a range of groups, including those at disadvantage. Funding: UK Medical Research Council (MR/KO 023209/1), Chief Scientist Office, NHS Health Scotland.